Polycyclic aromatic hydrocarbon contamination along roads based on levels on vehicle window films. (15th June 2021) - Zhang, Weiwei; Su, Penghao; Tomy, Gregg T.; Sun, Dan; Yin, Fang; Chen, Lisu; Ding, Yongsheng; Li, Yifan; Feng, Daolun
Abstract: Vehicular emissions are known to be major contributors of airborne polycyclic aromatic hydrocarbons (PAHs) in cities. In order to assess the long-term contamination of PAHs along roads, we collected organic films from vehicle windows (26 private cars and 4 buses, in Shanghai, China) and used mathematical models to convert the film-bound PAH concentrations to the airborne PAH concentrations. The field measurements of airborne PAHs revealed that the partitioning and Level III fugacity model was suitable to estimate the airborne concentrations of high and low volatile PAHs (expect for naphthalene), respectively. The total airborne PAH concentrations along roads in Shanghai ranged from 0.83 to 3.37 μg m −3 and the incremental lifetime cancer risks ( ILCR total ) by exposure to PAHs along roads were greater than the USEPA lower guideline of 10 −6, indicating non-negligible carcinogenic risks to drivers and passengers, especially via ingestion processes. This study provided a practicable method to investigate long-term air contamination of PAHs in vehicles and along roads based on film-bound PAH on vehicle windows. In addition, it was also possible to investigate the health risk in vehicles as a result of exposure to PAHs. Comparisons of PAHs between roads and shipping lanes also facilitated the delineation of vehicular and shipping PAH inventories. A capsule that summarizes the main finding of the work: Investigating film-bound PAH on vehicle windows is a practicable pathway to investigate the long-term contamination of PAHs in vehicles and along roads. This method can not only simplify the sampling processes, but the model calculations. The results also enabled investigations into ILCR in vehicles and specified source apportionment of traffic PAHs. Graphical abstract: Image 1 Highlights: High concentration of PAHs are detected in organic films on vehicle windows. Partitioning and fugacity model was reliable to estimate LMW and HMW PAHs in air, respectively. PAH compositions in vehicle air were generally consistent with newly emitted exhausts. PAHs posed considerable risks to passengers in Shanghai. The PAH contamination characteristics were different between vehicles and ships.